The Genetic Basis of Composite Spike Form in Barley and 'Miracle-Wheat'. Issue 1 (7th July 2015) - Poursarebani, Naser; Seidensticker, Tina; Koppolu, Ravi; Trautewig, Corinna; Gawroński, Piotr; Bini, Federica; Govind, Geetha; Rutten, Twan; Sakuma, Shun; Tagiri, Akemi; Wolde, Gizaw M; Youssef, Helmy M; et al.
Abstract: Inflorescences of the tribe Triticeae, which includes wheat ( Triticum sp. L.) and barley ( Hordeum vulgare L.) are characterized by sessile spikelets directly borne on the main axis, thus forming a branchless spike. 'Compositum-Barley' and tetraploid 'Miracle-Wheat' ( T. turgidum convar. compositum (L.f.) Filat.) display noncanonical spike-branching in which spikelets are replaced by lateral branch-like structures resembling small-sized secondary spikes. As a result of this branch formation 'Miracle-Wheat' produces significantly more grains per spike, leading to higher spike yield. In this study, we first isolated the gene underlying spike-branching in 'Compositum-Barley, ' i.e., compositum 2 ( com2 ). Moreover, we found that COM2 is orthologous to the branched head t ( bh t ) locus regulating spike branching in tetraploid 'Miracle-Wheat.' Both genes possess orthologs with similar functions in maize BRANCHED SILKLESS 1 ( BD1 ) and rice FRIZZY PANICLE/BRANCHED FLORETLESS 1 ( FZP / BFL1 ) encoding AP2/ERF transcription factors. Sequence analysis of the bh t locus in a collection of mutant and wild-type tetraploid wheat accessions revealed that a single amino acid substitution in the DNA-binding domain gave rise to the domestication of 'Miracle-Wheat.' mRNA in situ hybridization, microarray experiments, and independent qRT-PCR validation analyses revealed that the branch repression pathway in barley is governed through the spike architecture gene Six-rowed spike 4 regulating COM2 expression, while HvIDS1 (barley ortholog of maize INDETERMINATE SPIKELET 1 ) is a putative downstream target of COM2 . These findings presented here provide new insights into the genetic basis of spike architecture in Triticeae, and have disclosed new targets for genetic manipulations aiming at boosting wheat's yield potential.